2018
DOI: 10.1111/jep.12876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of parental reports to estimate health care resource utilization in children with suspected genetic disorders

Abstract: Parental surveys are a valuable tool for estimating health care resource utilization during a 6-month recall period for children with suspected genetic disorders but are best used to complement utilization data collected from other sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The discrepancy between reports and records could have been due to either incomplete medical record ascertainment or over-reporting by mothers; we did not have records for visits at sites not affiliated with the primary HCP. Accuracy in parental recall of the type and frequency of health care service visits has been shown to be quite variable, with recall of hospitalizations generally considerably better than that of emergency department or outpatient visits [35]. In our sample, recall of a visit after one week was accurate in only 50% of four hospitalizations recorded by automated survey in the first year of life; this proportion was not statistically different from that for visits to emergency, urgent or primary care.…”
Section: Discussionmentioning
confidence: 61%
“…The discrepancy between reports and records could have been due to either incomplete medical record ascertainment or over-reporting by mothers; we did not have records for visits at sites not affiliated with the primary HCP. Accuracy in parental recall of the type and frequency of health care service visits has been shown to be quite variable, with recall of hospitalizations generally considerably better than that of emergency department or outpatient visits [35]. In our sample, recall of a visit after one week was accurate in only 50% of four hospitalizations recorded by automated survey in the first year of life; this proportion was not statistically different from that for visits to emergency, urgent or primary care.…”
Section: Discussionmentioning
confidence: 61%
“…In prior work, we have shown that the sample of caregivers who completed the survey was broadly representative of the overall CAUSES sample, and that the risk of non-response bias is low. 29 Travel and time costs and estimated actual or potential cost savings from using TH are shown in Table 2. Average per-family total travel and time costs to visit C&W were Can$383 (SD = Can$631) for families who conducted in-person counselling through CAUSES as compared to Can$1043 (SD = Can$1177) for families who chose TH ( p = 0.008), while average costs to visit their local GP were Can$57 (SD = Can$106) and Can$78 (SD =Can $137), respectively ( p = 0.39).…”
Section: Resultsmentioning
confidence: 99%
“…chromosomal microarray analysis). [29][30][31][32][33] In addition to British Columbia, families residing in the province of Alberta and the Yukon Territory who were followed at BC Children's Hospital were invited to participate in the CAUSES Study. All families received pre-and post-test genetic counselling.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, we used data linkage to provide robust and comprehensive data on a large proportion of the healthcare costs, such as the hospital admissions and the utilization of healthcare resources listed under Medicare. When available, administrative data provide a reliable source of data compared to study participants’ recollection of events [ 3 ]. Data such as that collected in our study are important for capturing the wide-ranging healthcare and societal costs associated with familial ID in order to understand the broad financial impact on families and the government.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of familial ID is classified according to the intelligence quotient (IQ) of the affected person, as follows: mild (IQ 50-69), moderate (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and profound (<20) [2]. The global prevalence of ID is approximately 1%, with an estimated 20-50% of all ID cases of being of genetic etiology, and 450 identified genes are known to cause ID [3]. In Australia, roughly 450,000 (1.8%) of the population was estimated to have ID in 2021 [4].…”
Section: Introductionmentioning
confidence: 99%